Implementasi Manajemen POAC dalam Meningkatkan Kualitas Pengelolaan Zakat pada BAZNAS Kabupaten Asahan - Indria Karnilawati; Syahrul Amsari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This examination means to decide the use of POAC the executives at BAZNAS Asahan Rule, to decide the nature of zakat the board at BAZNAS Asahan Regime in view of POAC the board. The exploration approach utilized is a subjective examination technique with a clear methodology. Information assortment strategies utilized in this exploration are perception, meetings and documentation. The respondent in this examination is the Head of Branch The executives. In zakat services, the implementation of management functions is a unified whole in which positions are interconnected. The executives is the main piece of an establishment or association that will direct or move the foundation or association. As the Public Zakat Amil Organization, Asahan Regime has formed the execution of zakat administration the board, including Arranging, Coordinating, Inciting/Coordinating, Oversight. Aside from that, there are supporting and repressing elements for the assistance the board of zakat amil organizations. In light of the introduction of information and examination results with respect to the execution of POAC the board in working on the nature of Zakat the executives at BAZNAS Asahan Regime, the creator can reason that it has gone very well by having an unmistakable arrangement consistently. The association depends on the capacities of the amil in their separate fields. Bearings are completed by branch heads each prior day doing exercises. The job descriptions for each section determine how the movements are carried out. Control is completed by the top of the branch, then, at that point, management of the exercises and funds of BAZNAS Asahan Rule is done by the administrative center with an organized framework and evaluated by the administrative center.